Industrial Project Management International Standards and Best Practices for Engineering and Construction Contracting - Tonchia, Stefano (Management for Professionals, 2018)
This book describes the principles and techniques in Project Management as applied to Engineering & Construction Contracts (ECC), conforming with relevant international standards (PMI - IPMA - ISO 21500), and pursuing a fully company-wide, process-based, multi-project approach. Uniquely, the book combines Project Management fundamentals with international contracting practices, which shape the planning, design and construction of large and complex works (such as plants, machinery, infrastructures and buildings) worldwide. The rigorous academic approach is mixed with the managerial contributions of Danieli, one of the world's top three suppliers of plants and equipment to the metals industry. The book has been updated to reflect the PMBOK 6th edition (September 2017), presents best practices in PM from around the globe, and addresses new trends in PM such as Agile, SCRUM, etc. Lastly, a dedicated section covers the professional use of the reference software Microsoft Project.